(untitled) (NPRC Journal of Multidisciplinary Research, 2026)
Background: Management Information Systems (MIS) are fundamental for operational efficiency in modern banking. This study investigates MIS practices within Nepalese commercial banks, focusing on Nepal Bank Limited (NBL), which is transitioning to a unified Core Banking Software (CBS) to centralize operations. Objective: The primary objective is to analyze MIS practices at NBL, with a specific focus on assessing how information flows through network media and software across various management levels and departments to support decision-making and service delivery. Methods: Using a descriptive research design, data were collected from 60 NBL employees in the Kathmandu Valley via questionnaires (judgmental sampling), supplemented by secondary sources. Analysis employed descriptive statistics and exploratory factor analysis. Findings: Results indicate that MIS is widely used for decision support, data access, and secure information management, significantly enhancing managerial effectiveness and service delivery. However, the reliance on older software (Pumori) and identified gaps in employee analytical skills and process efficiency present constraints. Conclusion: MIS is a vital contributor to NBL’s operational management. For sustained competitiveness, strategic upgrades and focused human resource development are essential. Implementation: To optimize MIS benefits, NBL should: 1) Prioritize the complete deployment of modern, integrated CBS; 2) Establish separate, specialized MIS and IT departments; 3) Implement regular, mandatory training programs to enhance staff proficiency and analytical capabilities; and 4) Streamline lengthy procedural workflows through system-driven automation.